2001
DOI: 10.1002/bmc.34
|View full text |Cite
|
Sign up to set email alerts
|

Identification of reaction products of methamphetamine and hydrogen peroxide in hair dye and decolorant treatments by high‐performance liquid chromatography/mass spectrometry

Abstract: The effect of hydrogen peroxide, a main component of hair dye and decolorant treatments, on methamphetamine (MA) was studied. Two analytical methods, thin-layer chromatography (TLC) and high-performance liquid chromatography/mass spectrometry (LC/MS), were used for the separation and identification of MA derivatives. Mixtures of MA solutions and hydrogen peroxide that had been incubated at 39 degrees C for 24 h were shown to contain para-hydroxy MA by TLC and para-, meta- and ortho-hydroxy MAs by LC/MS. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our finding that the concentration of cocaine decreased after incubation with hydrogen peroxide agreed with that of Yegles et al (2000). In our previous report, we found that MA changed to three compounds (ortho-, meta-and parahydroxy MAs) and two other intermediate compounds (MA N-oxide and N-hydroxy MA) in the presence of hydrogen peroxide (Tanaka et al, 2001). However, in the present study, we did not find intermediate compounds in the reaction of cocaine and hydrogen peroxide.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Our finding that the concentration of cocaine decreased after incubation with hydrogen peroxide agreed with that of Yegles et al (2000). In our previous report, we found that MA changed to three compounds (ortho-, meta-and parahydroxy MAs) and two other intermediate compounds (MA N-oxide and N-hydroxy MA) in the presence of hydrogen peroxide (Tanaka et al, 2001). However, in the present study, we did not find intermediate compounds in the reaction of cocaine and hydrogen peroxide.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, we assumed that MA and AP were degraded by the hair dye or decolorant treatments (Takayama et al, 1999). Recently, we detected ortho-, meta-and parahydroxy MAs by high-performance liquid chromatography/mass spectrometry (LC/MS) after incubating a mixture of MA and hydrogen peroxide, the main component of hair dye and decolorant treatments (Tanaka et al, 2001). In addition, we found that MA changed to MA N-oxide and N-hydroxy MA before changing to ortho-, meta-and para-hydroxy MAs by the oxidative action of hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations would support the hypothesis that MA and AP are degraded in hair by dye and decolorant treatments. Recently, Tanaka et al (2001) found that MA changed to o-, m-and pOHMA isomers in the presence of hydrogen peroxide at 39°C using LC/MS/MS. Several studies have examined the effect of permanent and bleach treatments on other illegal drugs such as morphine and codeine (Potsch and Skopp, 1996;Skopp et al, 1997;Jurado et al, 1997;Yegles et al, 2000), cocaine (Jurado et al, 1997;Yegles et al, 2000), and tetrahydrocannabinol (Jurado et al, 1997).…”
Section: Distribution Of Ma and Ap In Hairmentioning
confidence: 99%
“…Ortho-, meta-and para-hydroxy methamphetamine were detected next to methamphetamine N-oxide and N-hydroxy methamphetamine. However, the study was never continued beyond the investigation of solutions, and detectability in authentic hair samples has yet to be discussed [40]. Doxylamine concentrations in authentic hair samples decreased through oxidative dyeing procedures, while an increase in the oxidation product N-doxylamineoxide was observed [41].…”
Section: Indirect Approaches: Oxidation Markers Of Drugsmentioning
confidence: 99%